A formação profissional dos egressos do Instuto Federal do Espírito Santo - Campus Ibaba dos Anos 2011-2017. Para além da formação técnica? - Cabral, Wilson Augusto Costa (2020)
The present study originated from the reflection on the question of the qualification of the worker, expropriated/alienated from the means of production and from the fruits of his work in the context of the destructive regressive crisis of capital. When addressing the issue of worker training at the Federal Institute of Science and Technology of Espírito Santo – Ifes – Campus Ibatiba the thesis discusses the issue of professional qualification at Federal Institutes. Was this formation reproducing social relations of production or counter-hegemonic? In his proposal, the central question ends: whether the teaching of Ifes Ibatiba is a teaching aimed at terminality – professional qualification in a specific area, with the consequent containment of graduates in their access to higher education –; or does it present itself as an opportunity for continued access to university? When taking the case of a concrete campus as a reference, it takes with analyze the formation of its graduates in the first four years since its creation. Taking the historical-dialectical method as a reference, the study bases its reflection on the dialectical concrete situation of worker training in the context of capitalist hegemony. When analyzing the policies that led to the creation of the Federal Education Network, it appears that it presents itself as the achievement of a government policy and not a State policy. In a look at the reality of the Ifes – Campus Ibatiba it appears that there is progress in its pedagogical proposal in relation to the reality of educational institutions in the region of the municipality, as well as limitations to be overcome. Using a double methodology to collect material – first a Google Docs questionnaire, sent to all graduates of the period in question and later an interview with a selected group – the work aimed at observing teaching at Ifes – Ibatiba from experience of those who experienced this process. It is concluded from the data presented by the research that although, in a reality dialectically marked by the hegemony of capital, the formation of Ifes – Ibatiba in the years 2011 to 2017 enabled a transformation in the life of its graduates, by opening them the possibility of access to higher education courses, previously seen as inaccessible by them. Such a reality at the level of micro-reproduction of social relations of production is presented as an achievement, although in the dynamics of macro-reproduction they are still subject to the ailments of the market and capital.